2000
DOI: 10.3758/bf03212088
|View full text |Cite
|
Sign up to set email alerts
|

Reaching measures of monocular distance perception: Forward versus side-to-side head movements and haptic feedback

Abstract: Weinvestigated whether forward or side-to-side head movements yielded more accurate and precise monocular egocentric distance information, as shown by performance in a reaching task. Observers wore a head-mounted camera and display to isolate the optic flow generated by their head movements and had to reach to align a stylus directly under a target surface. Performance in the two head movement conditions was also tested with normal monocular vision. Wetested performance in the two head movement conditions when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 21 publications
(30 reference statements)
5
30
0
Order By: Relevance
“…This result replicates the finding that haptic feedback resulting from contact with actual targets produces calibration and it allows reaches to become more precise Wickelgren, McConnell, & Bingham, 2000; see also Bingham, Zaal, Robin, & Shull, 2000;, even though it does not necessarily correct shape distortions (Bingham et al, 2001). Interestingly, we found an increase in precision even if haptic feedback was provided only to a predictable subset of prehension movements directed to a different spatial target.…”
Section: Effect Of Intermixed Haptic Feedback On Grasping Precisionsupporting
confidence: 82%
“…This result replicates the finding that haptic feedback resulting from contact with actual targets produces calibration and it allows reaches to become more precise Wickelgren, McConnell, & Bingham, 2000; see also Bingham, Zaal, Robin, & Shull, 2000;, even though it does not necessarily correct shape distortions (Bingham et al, 2001). Interestingly, we found an increase in precision even if haptic feedback was provided only to a predictable subset of prehension movements directed to a different spatial target.…”
Section: Effect Of Intermixed Haptic Feedback On Grasping Precisionsupporting
confidence: 82%
“…Further studies on reaching under monocular viewing conditions by Bingham and Stassen (1994) confirmed the finding that head movements in the direction of the target facilitate the recovery of its absolute distance (Pagano & Bingham, 1998). However, these results are specific for reaching space and, in some cases, refer to experimental conditions in which other types of sensory information were available, such as haptic feedback (Wickelgren, McConnell, & Bingham, 2000). Our study extends the investigation well beyond reaching space and was conducted with standing subjects performing head movements of larger amplitudes in unrestrained conditions.…”
Section: Head-generated Retinal Motion and Distance Estimationmentioning
confidence: 57%
“…The apparent conflict can be reconciled by the fact that reports of inaccurate distance perception have come from situations in which participants received no feedback about the outcome of their movement (i.e., they remained in a visual-open-loop environment throughout the experiment). In line with this, a number of research studies have demonstrated that reaches increasingly drift from visually targeted locations as feedback information is removed (Bingham, Zaal, Robin, & Shull, 2000;Vindras & Viviani, 1998;Wann & Ibrahim, 1992;Wickelgren, McConnell, & Bingham, 2000). These observations paint a picture of a nervous system that continually needs to adapt its behavior because it is subject to biological noise.…”
mentioning
confidence: 86%